2018
DOI: 10.1101/283788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The first next-generation sequencing approach to the mitochondrial phylogeny of African monogenean parasites (Platyhelminthes: Gyrodactylidae and Dactylogyridae)

Abstract: 27Background: Monogenean flatworms are the main ectoparasites of fishes. Representatives

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 106 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…These polymorphic tandem repeats were previously employed in studies of the population structures of medically important human parasites (e.g., Schistosoma haematobium, Gower et al, (2011)). However, they are still strongly underutilized in studies of parasitic platyhelminths in wildlife, as only a few papers focusing on cestodes (i.e., Luo, Nie, Zhang, Yao & Wang, 2003;Štefka, Hypša & Scholz, 2009;Umhang et al, 2018;Bazsalovicsová et al, 2020) or digeneans (i.e., Criscione, Cooper & Blouin, 2006;Louhi, Karvonen, Rellstab & Jokela, 2010;Criscione, Vilas, Paniagua & Blouin, 2011;Valdivia, Criscione, Cárdenas, Durán & Oliva, 2014;Dar, Vignoles, Rondeland & Dreyfuss, 2015;Juhásová et al, 2016;Vásquez et al, 2016;van Paridon, Colwell, Goater & Gilleard, 2017;Criscione, van Paridon, Gilleard & Goater, 2020) have so far been published. The above studies have shown that microsatellites, as molecular population markers, are more discriminative than rDNA and mtDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polymorphic tandem repeats were previously employed in studies of the population structures of medically important human parasites (e.g., Schistosoma haematobium, Gower et al, (2011)). However, they are still strongly underutilized in studies of parasitic platyhelminths in wildlife, as only a few papers focusing on cestodes (i.e., Luo, Nie, Zhang, Yao & Wang, 2003;Štefka, Hypša & Scholz, 2009;Umhang et al, 2018;Bazsalovicsová et al, 2020) or digeneans (i.e., Criscione, Cooper & Blouin, 2006;Louhi, Karvonen, Rellstab & Jokela, 2010;Criscione, Vilas, Paniagua & Blouin, 2011;Valdivia, Criscione, Cárdenas, Durán & Oliva, 2014;Dar, Vignoles, Rondeland & Dreyfuss, 2015;Juhásová et al, 2016;Vásquez et al, 2016;van Paridon, Colwell, Goater & Gilleard, 2017;Criscione, van Paridon, Gilleard & Goater, 2020) have so far been published. The above studies have shown that microsatellites, as molecular population markers, are more discriminative than rDNA and mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for the scarcity of published microsatellite studies on monogeneans (and population markers in general) remains the collection of appropriate material for NGS. As the quantity and quality of the genomic DNA isolated from a small-sized parasite may be insufficient, one option is to pool a considerable number of specimens (Vanhove, Briscoe, Jorissen, Littlewood & Huyse, 2018). However, considering that monogeneans are generally small-sized and that correct species identification is rather difficult without magnifying optical methods, there is a high risk of cross-species contamination in the pooled samples, rendering the obtained genomic data challenging to process.…”
Section: Discussionmentioning
confidence: 99%